Translocation of southern mountain caribou using a soft-release technique - Mathieu, Amélie; Vander Vennen, Lucas M.; Ried, Aaron; Legebokow, Cory; Schwantje, Helen M. (Rangifer, 2022)
Southern mountain caribou (Rangifer tarandus caribou, SMC) in British Columbia, Canada, are experiencing a precipitous population decline and range recession. In 2019, the two southernmost herds, the South Selkirks and the Purcells-South herds, were functionally extirpated and facing imminent extinction. To rescue the remaining animals, a translocation into the Columbia North herd range was performed using a soft-release method. The translocated animals were released alongside a captive-reared yearling and a resident adult female from the Columbia North SMC herd. A comparison of habitat selection behaviours at the 2nd order of selection demonstrated that the released animals responded to habitat and elevational conditions similarly to resident caribou. The translocation and soft release of Purcells-South and South Selkirks individuals demonstrates that soft release of wild translocated and captive-reared SMC can be successful and should be considered where and when feasible.